ANALISIS PENGARUH TINGKAT SUKU BUNGA TERHADAP JUMLAH UANG BEREDAR DI INDONESIA PERIODE 2018-2023 - Mutia Annisa; Nakita Nakita; Albi Sutandi (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2024)
The aim of this research is to determine the effect of interest rates on the amount of money circulating in Indonesia for the 2018 - 2023 period. The type of data in this research uses quantitative data and the data source used is secondary data for the 2018-2023 period. Data analysis uses a simple linear regression analysis method. The results of this research show that the interest rate variable does not have a significant influence on the money supply in Indonesia.